2007
DOI: 10.1139/v07-007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison study of live cells by atomic force microscopy, confocal microscopy, and scanning electrochemical microscopy

Abstract: In this report, three kinds of scanning probe microscopy techniques, atomic force microscopy (AFM), confocal microscopy (CM), and scanning electrochemical microscopy (SECM), were used to study live cells in the physiological environment. Two model cell lines, CV-1 and COS-7, were studied. Time-lapse images were obtained with both contact and tapping mode AFM techniques. Cells were more easily scratched or moved by contact mode AFM than by tapping mode AFM. Detailed surface structures such as filamentous struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…A wide variety of local surface modifications have been accomplished by the feedback mode. These include metal deposition, 31 [59][60][61][62][63][64][65][66][67][68][69] and, in a few cases, also modification. 70 Here we present an approach, termed scanning electrochemical imprinting microscopy, which combines the elements of SPM and printing.…”
mentioning
confidence: 99%
“…A wide variety of local surface modifications have been accomplished by the feedback mode. These include metal deposition, 31 [59][60][61][62][63][64][65][66][67][68][69] and, in a few cases, also modification. 70 Here we present an approach, termed scanning electrochemical imprinting microscopy, which combines the elements of SPM and printing.…”
mentioning
confidence: 99%
“…Unlike AFM, the SECM probe does not need to touch the cell, thus it can carry on time-lapse measurement without mechanically scratching the cell. Nevertheless, most SECM imaging experiments were conducted with the addition of a certain redox mediator, which is usually non- physiologic and undesired [7-9,11,12]. In our previous study [14], we found that dissolved oxygen in the medium solution could be detected by SECM, which provides an opportunity of label-free imaging cellular morphology using dissolved oxygen as the redox mediator.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, the real-time morphological changes of single live T24 cells under non-physiological temperature are revealed by time-lapse SECM with dissolved oxygen as the indicator. While the reactive oxygen species (ROS) released by live cells may interfere with the detection of dissolved oxygen [12,14,19], we determined that under physiological conditions oxygen can be reduced at -0.455 V and hydrogen peroxide can be reduced at -0.745 V, while superoxide is oxidized at +0.055 V. Thus in this research the potential was set at -0.500 V to reduce the dissolved oxygen. We also found that the resting status when the T24 cells do not release ROS can last for up to 5 h [20], which sustains imaging T24 cells with only dissolved oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations